Market coordination and the making of conventions: qualities, consumption and sustainability in the agro-food industry. - Evans, David M.; Mylan, Josephine (Economy & Society, 2019)
The coordination of activity across sites and spaces of production and consumption is a key concern for economic analysis. Joining a revival in the application of convention theory to agro-food scholarship, this paper considers complementary insights – related principally to 'the economy of qualities' – that animate different aspects of e/valuation, competition and alignment. These understandings are extended by more thoroughly acknowledging contemporary developments in consumption scholarship. The arguments are advanced through a case study of the orange juice market, linking its current high-carbon trajectory to the commercial and cultural significance of freshness. The analysis offers new insights into distributed processes of qualification as well as the mechanisms through which conventions are assembled and sustained. Finally, a more integrated approach to food production and consumption is outlined.